New cranial characters in the tribe Hydropsini (Serpentes: Dipsadidae: Xenodontinae) - Di Pietro, Diego Omar (2014)
We here describe the skull in four species of the three genera of the tribe Hydropsini (Serpentes: Dipsadidae: Xenodontinae): Helicops infrataeniatus, H. leopardinus, Hydrops caesurus and Pseudoeryx plicatilis. We compare them with several genera of Dipsadidae. We found that the unpaired foramen on the parabasisphenoid with anterior position is the only skull feature shared by all Hydropsini genera. This feature also occurs in semi-aquatic (Erythrolamphrus semiaureus) and fully-aquatic (Farancia abacura) dipsadids. All species of Hydrops with available skull descriptions and Pseudoeryx plicatilis share four features: (1) The anterior border of the angular is higher than the posterior border of the splenial, (2) the vomerine processes of the premaxilla are long, (3) the ascending process of the premaxilla overlaps the horizontal lamina of the nasals, and (4) an anterior projection of the prefrontal is present. All species of Helicops with available skull descriptions and Pseudoeryx plicatilis share three features: (1) A vertical lamina of the nasal with a notch, (2) a single foramen rotundum, and (3) the presence of a ventral projection of the transverse crista of the basioccipital. Finally, we found small, paired parietal foramina in most of the dipsadids studied here, which are filled with a Sudan-Black-positive tissue of possible nervous origin.